The Attitude of Trade Unions Towards Technological Changes - Peitchinis, Stephen (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
The author presents the results of a survey on the attitude of trade unions towards technological change.